Introduction to dental medicine: Analysis of a massive open online course in dentistry. Issue 1 (2nd September 2020) - France, Katherine; Hangorsky, Uri; Wu, Chia‐Wei; Sollecito, Thomas P.; Stoopler, Eric T.
Abstract: Objectives: This study aims to: (1) assess learner demographics of Introduction to Dental Medicine (IDM), an early Massive Open Online Course (MOOC) developed for the Coursera platform and (2) analyze course enrollment to determine worldwide interest in accessible, high‐quality dental education. Methods: The authors review the development and organization of IDM and present learner statistics to critically evaluate learner traits and course engagement for IDM. Results: IDM has been available since June 15, 2015, and as of March 1, 2020, gained 90, 374 visitors, of whom 16, 739 have enrolled and demonstrate continued monthly and daily engagement. Learners represent all age groups and genders and include participants of all educational and employment backgrounds, reflecting broad interest in dental knowledge. They originate from 6 continents with the largest percentages of learners from countries including the United States, Egypt, India, and the United Kingdom. IDM learners have provided positive feedback, rating the course 4.8/5 stars and often providing individual accounts of the benefit of their experiences. Conclusions: IDM presented an opportunity to learn general dental concepts. The course served to increase familiarity in the field for all learners, including health professionals, patients, and anyone with an interest in the subject. It also served as preparation for or to expand education in dental, medical, and allied health professions. High learner engagement with wide global distribution demonstrated interest in dental education worldwide.